The use of CAD/CAM technologies in minimally invasive dental restorations: a systematic review - Melnyk, N.; Chertov, S.O.; Jafarov, R.; Karavan, Ya.; Belikov, O.; Чертов, Сергій Олександрович (My University, 2025)
Aim of the study The study reviews dental treatment effectiveness, CAD/CAM technology compatibility, and restorative materials' clinical performance, focusing on demographics, criteria, interventions, methodologies, and outcomes across countries and follow-up durations. Materials and methods This systematic review evaluates CAD/CAM technologies in minimally invasive dental restorations, analyzing 10 relevant studies from the PubMed database published between 2019 and 2024 using specific keywords: “CAD/CAM” OR “computer-aided design” OR “computer-aided manufacturing” OR “digital dentistry” AND “minimally invasive” OR “conservative dentistry” AND “dental restoration” OR “dental crowns” OR “inlays” OR “onlays” OR “veneers” to assess their effectiveness in enhancing precision, reducing chair time, and improving materials for crowns, inlays, onlays, and veneers, while acknowledging limitations in inclusion criteria and study types. Results The systematic review on CAD/CAM technologies in minimally invasive dental restoration highlights studies from various countries, mostly randomized controlled trials, with sample sizes ranging from 20 to 90 patients. Follow-up durations span from 1 to 7.7 years. The studies cover diverse demographics, targeting different tooth types and dental conditions. CAD/CAM systems like CEREC and TRIOS, alongside materials such as nano-ceramics, zirconia, and composites, were used for various restoration types. Clinical outcomes revealed differences in survival rates, failure rates, and complications, emphasizing the importance of material and technique selection for optimal CAD/CAM restoration results. Conclusions The systematic review demonstrates CAD/CAM technology's global adoption, versatility in dental restorations, and varied performance outcomes, emphasizing the importance of material and technique selection for optimal long-term results.
Keywords: CAD/CAM; computer-aided design; computer-aided manufacturing; digital dentistry; conservative dentistry; dental restoration